2023
DOI: 10.2147/idr.s412669
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Analysis and Mortality Risk Factors in Patients with Polymicrobial Bloodstream Infections

Abstract: Purpose To study the etiological characteristics and risk factors affecting the prognosis of patients with polymicrobial bloodstream infections. Patients and Methods Overall, 141 patients with polymicrobial bloodstream infections in Henan Provincial People’s Hospital during 2021 were included. Laboratory test indexes, department of admission, sex, age, intensive care unit (ICU) admission, surgical history, and central venous catheter placement were collected. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…We also found that patients with polymicrobial BSIs had a longer median length of hospital stay than patients with monomicrobial BSIs, but the differences were not statistically significant. A similar finding has been reported from previous studies, which found polymicrobial BSIs increase the risk of mortality [ 11 , 15 ]. The difficulties in selecting appropriate empiric antimicrobials targeting multiple pathogens and delays in reporting blood culture results could impact our study’s observed findings.…”
Section: Discussionsupporting
confidence: 91%
“…We also found that patients with polymicrobial BSIs had a longer median length of hospital stay than patients with monomicrobial BSIs, but the differences were not statistically significant. A similar finding has been reported from previous studies, which found polymicrobial BSIs increase the risk of mortality [ 11 , 15 ]. The difficulties in selecting appropriate empiric antimicrobials targeting multiple pathogens and delays in reporting blood culture results could impact our study’s observed findings.…”
Section: Discussionsupporting
confidence: 91%
“…In human, bloodstream polymicrobial infections often occur in patients with poor medical conditions (XU et al, 2023). The risk factors for these infections include diabetes, chronic liver diseases, cardio vascular diseases, immunosuppressive diseases, hematologic diseases, and tumors (XU et al, 2023). In our study, blood coinfection was identified among the canines with or without Leishmania infection, and many dogs showed poor health and nutritional conditions.…”
Section: Discussionmentioning
confidence: 62%
“…In fact, many infectious diseases of hu mans and animals are caused by more than one microorganism from different kingdoms, gene ra, species, and by phenotypic variants of a sin gle species (Bakaletz, 2004). In human, bloodstream polymicrobial infections often occur in patients with poor medical conditions (XU et al, 2023). The risk factors for these infections include diabetes, chronic liver diseases, cardio vascular diseases, immunosuppressive diseases, hematologic diseases, and tumors (XU et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that one-third of hospital-associated deaths were related to sepsis, and bacterial infections causing sepsis account for 87% of hospitalizations [1]. Xu et al found that among 1318 patients with positive blood cultures in China, the associated mortality rate was 48.9% [2]. The GBD 2019 Antimicrobial Resistance Collaborators estimated that deaths caused by 33 bacterial pathogens accounted for 13.6% of all global deaths and 56.2% of all sepsis-related deaths in 2019 [3].…”
Section: Introductionmentioning
confidence: 99%
“…For ceftobiprole, almost no activity was observed against ESBL-positive Enterobacterales, with resistance rates ranging from 78.6% to 100.0% (Table 3). 2 MIC 50 : minimum inhibitory concentration that inhibits 50% of bacterial isolates tested. 3 MIC 90 : minimum inhibitory concentration that inhibits 90% of bacterial isolates tested.…”
Section: Introductionmentioning
confidence: 99%